Glass fiber reinforced plastic and preparation method thereof

Through the combination of silicon modified glass fiber and epoxy phenol resin, the problem of degradation of flame retardant performance of glass fiber reinforced plastics at high temperatures is solved, and the high temperature resistance and good flame retardant performance of the material is achieved, reducing flammability and harmfulness Emissions meet strict safety standards.

CN119177006AInactive Publication Date: 2024-12-24GUANGZHOU FUZHOU TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538736.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing glass fiber reinforced plastics have deteriorated flame retardant properties in high temperature environments, and there are safety hazards for flammability and toxic gas emissions, which are difficult to meet specific safety requirements.

Method used

Silicon modified glass fiber and epoxy phenol resin are used as substrates to improve the high temperature resistance and flame retardant properties of the material through the modification process. Combined with fillers and light absorbers and other components, we can prepare a good stiffness, flexibility and ductility. Fiberglass reinforced plastic.

Benefits of technology

It significantly improves the high temperature resistance and flame retardant properties of the material, reduces flammability, delays combustion, reduces hazardous waste emissions, and complies with strict safety standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a glass fiber reinforced plastic and a preparation method thereof, and belongs to the technical field of glass fiber reinforced plastics. The glass fiber reinforced plastic comprises the following components in percentage: 25%-35% of modified glass fiber, 40%-60% of modified epoxy phenol resin, 3%-5% of a hardener, 3%-5% of an initiator, 0.5%-3% of an antioxidant, 0.5%-3% of a light absorber and 5%-10% of a filler. According to the invention, the modified glass fiber and the modified epoxy phenol resin are used as matrixes, so that the high-temperature-resistant composite material has relatively strong high-temperature resistance, meanwhile, relatively excellent strength and wear resistance are obtained through the cross-linking action of the resin, and the high-temperature-resistant composite material is suitable for being applied to building materials and precise instruments working in contact with a fire source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass fiber reinforced plastics, and in particular to a glass fiber reinforced plastic and a preparation method thereof. Background Art

[0002] Glass fiber reinforced plastic is a composite material with a wide variety of products and good performance. Its development background can be traced back to the mid-20th century. It is mainly composed of glass fiber and resin matrix. Glass fiber is used as a reinforcing material to provide high strength and stiffness. E-type glass fiber is usually used, and its characteristics include excellent tensile strength and stiffness. The resin matrix is ​​used as a binder and environmental protection layer for the glass fiber. Thermosetting resins such as epoxy resins, polyester resins or phenolic resins are usually selected. These resins can provide good corrosion resistance and chemical resistance. Overall, glass fiber reinforced plastics continue to develop and have been widely used in fields such as construction, transportation, energy and electronics.

[0003] At present, glass fiber reinforced plastics perform well under many environmental conditions. The Chinese patent with publication number CN118165440A discloses a glass fiber reinforced plastic and a preparation method thereof, which uses chitosan modified phenolic resin to obtain good strength and wear resistance of the prepared glass fiber reinforced plastic. However, the material used is flammable at high temperatures. Although the glass fiber itself has good fire resistance, the flammability of the resin matrix may affect the overall flame retardant performance and the glass fiber reinforced plastic may release toxic gases such as hydrogen chloride and carbon dioxide when burning, which are potential risks to the environment and health. Publication number CN111518362A provides a high-temperature flame-retardant glass fiber reinforced plastic and a preparation method thereof, which modifies the phenolic resin with silicon to make the phenolic resin partially heat-resistant and then enhances its flame retardant performance by filling fillers such as kaolin talc, but its flame retardant performance is relatively ordinary and there are organic waste gas emissions after combustion. Under high temperature environment, the flame retardant performance of glass fiber reinforced plastic may decrease. The thermal stability of the resin matrix is ​​limited, so the material may lose some of its flame retardant effect under high temperature conditions. In summary, although glass fiber reinforced plastics perform well in certain applications, their flame retardant properties still need to be properly designed and modified to meet specific safety requirements. Therefore, inventing a glass fiber reinforced plastic with good flame retardant properties is an urgent problem to be solved.

[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a glass fiber reinforced plastic and a preparation method thereof; the plastic can have strong rigidity and flexibility, and at the same time can obtain good ductility and high temperature resistance.

[0006] A glass fiber reinforced plastic is composed of the following ingredients in percentages: 25%-35% of modified glass fiber, 40%-60% of modified epoxy phenol resin, 3%-5% of hardener, 3%-5% of initiator, 0.5%-3% of antioxidant, 0.5%-3% of light absorber and 5%-10% of filler.

[0007] The preparation method of the modified epoxy phenol resin comprises the following steps:

[0008] A1: Add epoxy phenol resin and hydrochloric acid into deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30 minutes at a temperature of 100-120°C and a stirring rate of 500-600 rpm. After complete dissolution, adjust the temperature to 45-60°C, set the stirring rate to 300-400 rpm, and stir for 2 hours to obtain intermediate A.

[0009] A2: Add acrylate and cellulose to intermediate A, add organosilane coupling agent, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 30 minutes at a temperature of 30-45°C and a stirring rate of 400-600rpm, then increase the temperature and continue stirring and reacting for 5-6 hours under reflux conditions. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with distilled water for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 80-85°C for 3-5 hours to obtain intermediate B;

[0010] A3: Transfer intermediate B to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 10-15 min at a temperature of 50-55°C and a stirring rate of 300-400 rpm, then add phenol dropwise at a dropping rate of 1-2 drops / s, raise the temperature to 110-120°C after the addition is completed, and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the product to room temperature to obtain a modified epoxy phenol resin.

[0011] Furthermore, the concentration of the hydrochloric acid is 5%; and the organic silane coupling agent is KH-570.

[0012] Furthermore, in step 1, the mass ratio of hydrochloric acid to deionized water is 1:10; in step 2, the mass ratio of intermediate A, acrylate, cellulose and organosilane coupling agent is 10:2:5:1; and in step 3, the mass ratio of intermediate B to phenol is 10:1.

[0013] The preparation method of the modified glass fiber comprises the following steps:

[0014] B1: E-glass fiber and mica powder were mixed in deionized water and added into a three-necked flask equipped with a stirrer, a thermometer, a nitrogen gas guide tube and a reflux condenser. Nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 75-80°C and a stirring rate of 400-600rpm for 30 minutes. The mixture was then heated to reflux and stirred for reaction for 2-3 hours. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed with distilled water for 3-5 times and then placed in a vacuum drying oven for drying at a temperature of 60-65°C for 2-3 hours to obtain a modified glass fiber intermediate 1.

[0015] B2: Add the modified glass fiber intermediate 1, polyethylene terephthalate and tetraisopropyl titanate into a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stir the reaction for 30 minutes at a temperature of 65-75°C and a stirring rate of 400-600rpm. Then, add an organic silane coupling agent and continue stirring the reaction for 2-3 hours under the condition of raising the temperature to reflux to obtain a modified glass fiber intermediate 2.

[0016] B3: The modified glass fiber intermediate 2 is transferred to a three-necked flask equipped with an agitator, a thermometer and a constant pressure dropping funnel, and sodium hydroxide solution is added dropwise at a temperature of 35-45°C and a stirring rate of 300-400rpm. The dropping rate is controlled to 1-2 drops / s and the pH is adjusted to 8-8.5. After the reaction is completed, the reaction product is cooled to room temperature and then vacuum filtered. The filter cake is washed with deionized water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 1-2h to obtain modified glass fiber.

[0017] Furthermore, the E-type glass fiber has a length of 3 mm and a diameter of 20 um; the concentration of the sodium hydroxide solution is 25%; and the organic silane coupling agent is KH-570.

[0018] Furthermore, in step 1, the mass ratio of E-type glass fiber and mica powder is 5:1; in step 2, the mass ratio of modified glass fiber intermediate 1, polyethylene terephthalate, tetraisopropyl titanate and organic silane coupling agent is 10:2:2:1.

[0019] A method for preparing glass fiber reinforced plastic comprises the following steps:

[0020] C1: Preparation of modified glass fiber

[0021] C2: Preparation of modified epoxy phenol resin

[0022] C3: The modified epoxy phenol resin and the hardener were mixed in a reaction kettle, stirred at 45-65° C. and 800-1200 rpm for 30 min, and then the coupling agent was added, and stirred at 65-70° C. and 800-1200 rpm for 120 min to obtain product A.

[0023] C4: Add filler to product A and steam heat to 65-90°C for 15 min. Set the speed to 600-800 rpm and stir for 1 h to evenly disperse the filler in the liquid.

[0024] C5: Add the light absorber and antioxidant into the reaction kettle, 55-60℃, 1000-1200rpm, then add the modified glass fiber into the reaction system, set the temperature to 160-180℃, set the speed to 300-500rpm and stir for 2h.

[0025] C6: After the reaction is completed, vacuum filter the mixture into a mold and solidify it for 0.5-1h to obtain glass fiber reinforced plastic.

[0026] In summary, due to the adoption of the above technical scheme, the beneficial effects of the present invention are as follows: the present invention uses silicon-modified glass fiber epoxy phenol resin as a matrix, which not only enables the plastic to obtain the strong impact resistance and flexibility of epoxy phenol resin, but also greatly reduces the flammability of epoxy phenol resin; the use of silicon-modified glass fiber can significantly improve the stiffness and high temperature resistance of glass fiber, and the plastic made by the coupling effect of the two not only has strong stiffness and flexibility, but also can obtain good ductility, and significantly improves the high temperature resistance, which has a lot of room for use in places that need to contact high temperature environment, such as building materials or the shells of precision materials that need to be resistant to high temperatures. DETAILED DESCRIPTION

[0027] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0028] The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0029] Example 1

[0030] 1. Add 120g of epoxy phenol resin and 20ml of hydrochloric acid to 200ml of deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30min at a temperature of 120°C and a stirring rate of 600rpm. After complete dissolution, adjust the temperature to 60°C, set the stirring rate to 400rpm, and stir for 2h to obtain intermediate A.

[0031] 2. Add 20g of acrylate and 50g of cellulose to 100g of intermediate A, add 12g of organosilane coupling agent KH-570, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 30min at a temperature of 30°C and a stirring rate of 600rpm, then increase the temperature and continue stirring and reacting for 5h under reflux conditions. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 3-5h to obtain intermediate B;

[0032] 3. Transfer 150g of intermediate B to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 15min at a temperature of 55°C and a stirring rate of 400rpm, then add 15ml of phenol dropwise, control the dropping rate to 1 drop / s, and after the addition is completed, heat to 120°C and continue stirring and reacting for 3h. After the end, cool the product to room temperature to obtain 150g of modified epoxy phenol resin.

[0033] Table 1, reagent parameters used in Example 1

[0034] Drug Name source model parameter Epoxy phenol resin Guangzhou Konari New Materials Co., Ltd. NPEF-170 500L hydrochloric acid Aladdin H399545 2.5L Acrylate Shandong Chenyou Materials Co., Ltd. AH-863 200kg Cellulose Jinan Chuanxi Chemical Industry Priority Company 9004-62-0 25kg Organic silane coupling agent Zhengzhou Jieyang Chemical Products Co., Ltd. KH-570 5kg phenol Aladdin P128316 2.5kg

[0035] Example 2

[0036] 1. Add 150g of epoxy phenol resin and 30ml of hydrochloric acid to 300ml of deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30min at a temperature of 100°C and a stirring rate of 500rpm. After complete dissolution, adjust the temperature to 45°C, set the stirring rate to 300rpm, and stir for 2h to obtain intermediate A.

[0037] 2. Add 28g of acrylate and 70g of cellulose to 140g of intermediate A, add 14g of organosilane coupling agent KH-570, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir the reaction at a temperature of 30°C and a stirring rate of 400rpm for 30min, then increase the temperature and continue stirring the reaction under reflux for 6h. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, the filter cake is washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 5h to obtain intermediate B;

[0038] 3. Transfer 200g of intermediate B to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 15min at a temperature of 50°C and a stirring rate of 400rpm, then add 20ml of phenol dropwise, control the dropping rate to 2 drops / s, and after the addition is completed, heat to 120°C and continue stirring and reacting for 3h. After the end, cool the product to room temperature to obtain 200g of modified epoxy phenol resin.

[0039] Table 2, reagent parameters used in Example 2

[0040] Drug Name source model parameter Epoxy phenol resin Guangzhou Konari New Materials Co., Ltd. NPEF-170 500L hydrochloric acid Aladdin H399545 2.5L Acrylate Shandong Chenyou Materials Co., Ltd. AH-863 200kg Cellulose Jinan Chuanxi Chemical Industry Priority Company 9004-62-0 25kg Organic silane coupling agent Zhengzhou Jieyang Chemical Products Co., Ltd. KH-570 5kg phenol Aladdin P128316 2.5kg

[0041] Example 3

[0042] 1. 50 g of E-type glass fiber and 5 g of mica powder were mixed in 100 ml of deionized water and added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen gas guide tube and a reflux condenser. Nitrogen protection was introduced, and the mixture was stirred for 30 min at a temperature of 80 ° C and a stirring rate of 600 rpm. Then, the mixture was heated to reflux and continued to stir for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 3 h to obtain 50 g of modified glass fiber intermediate 1;

[0043] 2. Add 50g of modified glass fiber intermediate 1, 10g of polyethylene terephthalate and 10g of tetraisopropyl titanate into a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, stir and react for 30min at a temperature of 75°C and a stirring rate of 600rpm, then add 5g of organic silane coupling agent KH-570 and continue stirring and reacting for 3h under the condition of heating to reflux to obtain 65g of modified glass fiber intermediate 2.

[0044] 3. Transfer 65g of the modified glass fiber intermediate 2 to a three-necked flask equipped with an agitator, a thermometer and a constant pressure dropping funnel, add sodium hydroxide solution dropwise at a temperature of 45°C and a stirring rate of 400rpm, control the dropping rate to 2 drops / s, and adjust the pH to 8.5. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with deionized water 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 65°C for 2h to obtain 65g of modified glass fiber.

[0045] Table 3, reagent parameters used in Example 3

[0046]

[0047] Example 4

[0048] 1. 100 g of E-type glass fiber and 10 g of mica powder were mixed in deionized water and added to a three-necked flask equipped with a stirrer, a thermometer, a nitrogen gas guide tube and a reflux condenser. Nitrogen protection was introduced, and the reaction was stirred for 30 min at a temperature of 75 ° C and a stirring rate of 400 rpm. Then, the temperature was raised to reflux and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 60 ° C for 3 h to obtain 100 g of modified glass fiber intermediate 1;

[0049] 2. Add 100 g of modified glass fiber intermediate 1, 20 g of polyethylene terephthalate and 20 g of tetraisopropyl titanate into a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, and stir the reaction for 30 min at a temperature of 65 ° C and a stirring rate of 400 rpm. Then, add the organosilane coupling agent KH-570 and continue stirring the reaction for 3 h under reflux conditions to obtain 110 g of modified glass fiber intermediate 2.

[0050] 3. Transfer 110g of modified glass fiber intermediate 2 to a three-necked flask equipped with an agitator, a thermometer and a constant pressure dropping funnel, add sodium hydroxide solution dropwise at a temperature of 45°C and a stirring rate of 300rpm, control the dropping rate to 1-2 drops / s, and adjust the pH to 8. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed 5 times with deionized water, and then placed in a vacuum drying oven and dried at a temperature of 65°C for 2h to obtain 110g of modified glass fiber.

[0051] Table 4, reagent parameters used in Example 4

[0052]

[0053] Example 5

[0054] 1. 40 g of modified epoxy phenol resin and 4 g of phthalic acid diester were mixed in a reactor, stirred at 65°C and 1200 rpm for 30 min, then 0.5 g of organosilane coupling agent KH-570 was added, and stirred at 70°C and 1200 rpm for 120 min to obtain product A.

[0055] 2. Add 5 g of aluminum hydroxide to product A and steam heat to 90°C for 15 min. Set the speed to 800 rpm and stir for 1 h to evenly disperse the aluminum hydroxide in the liquid.

[0056] 3. Add 3g of dibenzofuran and 3g of phenylene sulfide into the reaction kettle, 55-60°C, 1000-1200rpm, then add 35g of modified glass fiber into the reaction system, set the temperature to 180°C, set the speed to 500rpm and stir for 2h.

[0057] 4. After the reaction is completed, vacuum filter it into a mold and cure it for 1 hour to obtain glass fiber reinforced plastic.

[0058] Table 5, reagent parameters used in Example 5

[0059]

[0060] Table 6, Parameters of glass fiber reinforced plastics prepared in Example 5

[0061]

[0062]

[0063] Example 6

[0064] 1. 60 g of modified epoxy phenol resin and 3 g of tributyl phosphate were mixed in a reactor, stirred at 65°C and 1200 rpm for 30 min, and then 1 g of organosilane coupling agent KH-570 was added, and stirred at 70°C and 1200 rpm for 120 min to obtain product A.

[0065] 2. Add 10g of calcium carbonate to product A and steam heat to 90°C for 15 minutes. Set the speed to 800rpm and stir for 1 hour to evenly disperse the calcium carbonate in the liquid.

[0066] 3. Add 1.5g of p-hydroxybenzoic acid methyl ester and 1.5g of xylidine into the reactor at 60°C and 200rpm, then add 35g of modified glass fiber into the reaction system, set the temperature to 160°C and the speed to 500rpm and stir for 2h.

[0067] 4. After the reaction is completed, vacuum filter it into a mold and cure it for 1 hour to obtain glass fiber reinforced plastic.

[0068] Table 7, reagent parameters used in Example 6

[0069]

[0070] Table 8, Parameters of glass fiber reinforced plastics prepared in Example 6

[0071] Test items Test Standards Test Results Impact resistance / MPa GB / T 21122 652 Heat resistance / ℃ ISO 75-1 216 Flexibility / MPa GB / T 9341 222 Alkali resistance (50% NaOH) GB / T 12087 No abnormality <![CDATA[Acid resistance (10% H2SO4)]]> GB / T 12087 No abnormality Water resistance ISO 175-1 No abnormality Environmental protection level ISO 14000 No abnormality

[0072] Example 7

[0073] 1. Mix 50g of modified epoxy phenol resin and 4g of phthalic acid diester in a reactor, stir at 45°C and 1000rpm for 30min, then add 0.5g of organosilane coupling agent KH-570, stir at 65°C and 900rpm for 120min to obtain product A.

[0074] 2. Add 5g silica powder and 5g aluminum hydroxide to product A and steam heat to 90°C for 15 minutes. Set the speed to 700rpm and stir for 1 hour to evenly disperse the silica powder and aluminum hydroxide in the liquid.

[0075] 3. Add 1.5g of dibenzofuran and 1.5g of phenylene sulfide into the reactor at 60°C and 1000rpm, then add 35g of modified glass fiber into the reaction system, set the temperature to 180°C, the speed to 400rpm and stir for 2h.

[0076] 4. After the reaction is completed, vacuum filter it into a mold and cure it for 0.5h to obtain glass fiber reinforced plastic.

[0077] Table 9, reagent parameters used in Example 7

[0078]

[0079]

[0080] Table 10, Parameters of glass fiber reinforced plastics prepared in Example 7

[0081] Test items Test Standards Test Results Impact resistance / MPa GB / T 21122 645 Heat resistance / ℃ ISO 75-1 212 Flexibility / MPa GB / T 9341 203 Alkali resistance (50% NaOH) GB / T 12087 No abnormality <![CDATA[Acid resistance (10% H2SO4)]]> GB / T 12087 No abnormality Water resistance ISO 175-1 No abnormality Environmental protection level ISO 14000 No abnormality

[0082] Comparative Example 1

[0083] Example 1 with publication number CN111518362A was selected as comparative example 1.

[0084] Comparative Example 2

[0085] Example 1 with publication number CN118165440A was selected as comparative example 2.

[0086] Copper clad laminate inspection:

[0087] The uncured plastics in Examples 5-7 and Comparative Examples 1-2 were mixed with bisphenol A epoxy resin at an equivalent ratio of 1:1, and 1000 ppm of imidazole and 50% of the weight of aluminum hydroxide were added to the total resin. Ethanol was then added until the solid content of the mixture was 60%. After stirring evenly, the glass cloth was impregnated in the mixture, and then the impregnated glass cloth was placed in an oven at 150°C for 5 minutes to form a prepreg. 8 sheets of the prepreg were stacked together, and a layer of electrolytic copper foil was stacked on the upper and lower sides, and then pressed in a vacuum hot press to obtain a copper-clad laminate. The pressing conditions were: a pressure of 25 kg / cm2 and pressing at 220°C for 2 hours.

[0088] Among them, thermal weight loss T d 5% is measured according to the TGA test method specified in IPC-TM-650 2.4.24.6. The T288 solder resistance test method is to immerse the above-mentioned pressure cooker test piece in a 288°C solder furnace, record the time required for the test piece to burst and delaminate, and the evaluation is completed when the substrate has not bubbled or delaminated for more than 5 minutes in the solder furnace. Glass transition temperature test: Use a differential scanning calorimeter with a heating rate of 20°C / min. Flame retardancy test: Test the flame retardancy of the sample according to the UL-94 standard method.

[0089] Table 11, Performance test results of copper clad laminates of Examples 5-7 and Comparative Examples 1-2

[0090] Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 T288 solder resistance >600 >600 >600 >600 536 <![CDATA[Thermogravimetric T d 5% °C]]> 421.2 434.6 414.7 401.6 382.1 Glass transition temperature℃ 202.4 210.3 201.1 198.5 196.3 Flame retardancy test UL-94 V-0 V-0 V-0 V-0 V-1

[0091] From the analysis of the above table, it can be seen that Examples 5-7 have stronger high temperature resistance and flame retardancy.

[0092] Physical performance test:

[0093] The glass fiber reinforced plastics prepared in Examples 5-7 and Comparative Examples 1-2 were tested for physical properties.

[0094] The tensile strength is tested according to GB / T1447-2005 "Test method for tensile properties of fiber reinforced plastics"; the flexural strength is tested according to GB / T1449-2005 "Test method for flexural properties of fiber reinforced plastics"; the heat deformation temperature is tested according to GB / T1634.2-2004 "Determination of load deformation temperature of plastics" (A method).

[0095] Table 12, Physical property test results of Examples 5-7 and Comparative Examples 1-2

[0096] sample Tensile strength / MPa Bending strength / MPa Heat deformation temperature / ℃ Example 5 79 269 217 Example 6 93 282 234 Example 7 75 254 216 Comparative Example 1 71 211 209 Comparative Example 2 68 203 197

[0097] Non-flammable performance test:

[0098] The non-combustibility properties of the glass fiber reinforced plastics prepared in Examples 5-7 and Comparative Examples 1-2 were tested according to B / T8626-2007 “Test Method for Combustibility of Building Materials”.

[0099] Table 13, non-flammability test results of Examples 5-7 and Comparative Examples 1-2

[0100] Is it ignited? Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 Was the experiment ignited? no no no no yes Does the flame reach 150mm? no no no no yes Time to reach 150mm / / / / 20min Is the filter paper ignited? no no no no yes

[0101] Combustion level test:

[0102] The combustion performance grades of the glass fiber reinforced plastics prepared in Examples 5-7 and Comparative Examples 1-2 were tested according to G / B8624-2012 “Combustion Performance Classification of Building Materials and Products”.

[0103] Table 14, Combustion performance ratings of Examples 5-7 and Comparative Examples 1-2

[0104] Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 grade A-level A-level A-level B1 B2

[0105] From the non-combustible performance test and the combustion grade test, the glass fiber reinforced plastic prepared by the present invention not only has good flame retardant properties and can delay combustion when a fire occurs, but also has no harmful waste emissions during the combustion process, meets the FM standard, and can minimize fire damage.

[0106] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A glass fiber reinforced plastic, characterized in that: The following percentages of ingredients Composition: modified glass fiber 25%-35%, modified epoxy phenol resin 40%-60%, hardener 3%-5%, initiator 3%-5%, antioxidant 0.5%-3%, light absorber 0.5%-3% and filler 5%-10%; The modified epoxy phenol resin is prepared by the following steps: A1: Add epoxy phenol resin and hydrochloric acid into deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30 min at a temperature of 100-120°C and a stirring rate of 500-600 rpm. After complete dissolution, adjust the temperature to 45-60°C, set the stirring rate to 300-400 rpm, and stir for 2 h to obtain intermediate A; A2: Add acrylate and cellulose to intermediate A, add organosilane coupling agent, use a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 30 minutes at a temperature of 30-45°C and a stirring rate of 400-600rpm, then increase the temperature and continue stirring and reacting for 5-6 hours under reflux conditions. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with distilled water for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 80-85°C for 3-5 hours to obtain intermediate B; A3: Transfer intermediate B to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stir and react for 10-15 min at a temperature of 50-55°C and a stirring rate of 300-400 rpm, then add phenol dropwise at a dropping rate of 1-2 drops / s, raise the temperature to 110-120°C after the addition is completed, and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the product to room temperature to obtain a modified epoxy phenol resin.

2. A glass fiber reinforced plastic according to claim 1, characterized in that: The concentration of the hydrochloric acid in step A1 is 5%; the mass ratio of hydrochloric acid to deionized water is 1:

10.

3. A glass fiber reinforced plastic according to claim 1, characterized in that: In step A2, the mass ratio of intermediate A, acrylate, cellulose and organosilane coupling agent is 10:2:5:

1.

4. A glass fiber reinforced plastic according to claim 1, characterized in that: The mass ratio of intermediate B to phenol in step A3 is 10:

1.

5. The glass fiber reinforced plastic according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: B1: E-glass fiber and mica powder were mixed in deionized water and added into a three-necked flask equipped with a stirrer, a thermometer, a nitrogen gas guide tube and a reflux condenser. Nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 75-80°C and a stirring rate of 400-600rpm for 30 minutes. The mixture was then heated to reflux and stirred for reaction for 2-3 hours. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed with distilled water for 3-5 times and then placed in a vacuum drying oven for drying at a temperature of 60-65°C for 2-3 hours to obtain a modified glass fiber intermediate 1. B2: Add the modified glass fiber intermediate 1, polyethylene terephthalate and tetraisopropyl titanate into a three-necked flask equipped with a thermometer, a stirrer and a reflux condenser, stir and react for 30 minutes at a temperature of 65-75°C and a stirring rate of 400-600 rpm, then add an organic silane coupling agent and continue stirring and reacting for 2-3 hours under the condition of heating to reflux to obtain a modified glass fiber intermediate 2; B3: The modified glass fiber intermediate 2 is transferred to a three-necked flask equipped with an agitator, a thermometer and a constant pressure dropping funnel, and sodium hydroxide solution is added dropwise at a temperature of 35-45°C and a stirring rate of 300-400rpm. The dropping rate is controlled to 1-2 drops / s and the pH is adjusted to 8-8.

5. After the reaction is completed, the reaction product is cooled to room temperature and then vacuum filtered. The filter cake is washed with deionized water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 1-2h to obtain modified glass fiber.

6. A glass fiber reinforced plastic according to claim 5, characterized in that: The mass ratio of E-type glass fiber to mica powder in step B1 is 5:

1.

7. The glass fiber reinforced plastic according to claim 5, characterized in that: The mass ratio of the modified glass fiber intermediate 1, polyethylene terephthalate, tetraisopropyl titanate and organic silane coupling agent in step B2 is 10:2:2:

1.

8. The method for preparing glass fiber reinforced plastic according to claim 1, characterized in that: The following steps are involved: C1: Preparation of modified glass fiber; C2: Preparation of modified epoxy phenol resin; C3: The modified epoxy phenol resin and the hardener were mixed in a reaction kettle, stirred at 45-65°C and 800-1200 rpm for 30 min, and then the coupling agent was added, and stirred at 65-70°C and 800-1200 rpm for 120 min to obtain product A; C4: Add filler to product A and steam heat to 65-90℃ for 15min, set the speed to 600-800rpm and stir for 1h to evenly disperse the filler in the liquid; C5: Add the light absorber and antioxidant into the reaction kettle, 55-60°C, 1000-1200rpm, then add the modified glass fiber into the reaction system, set the temperature to 160-180°C, set the speed to 300-500rpm and stir for 2h; C6: After the reaction is completed, vacuum filter the mixture into a mold and solidify it for 0.5-1h to obtain glass fiber reinforced plastic.